Digital Social Media Influencers’ Impact on Beauty and Personal Care Purchases in South Africa - Raksha Singh; Arnesh Telukdarie; Regionald Mongwe (Platforms)
The South African beauty and personal care industry has been significantly impacted by digital technologies, with social media influencers (SMIs) playing a pivotal role in shaping consumer behaviour. Despite the significant role of SMIs, there is a notable research gap in optimising their influence to boost customer engagement and drive sales. This study addresses this gap by introducing a comprehensive digital framework integrating artificial intelligence (AI) and digitalisation to enhance influencer marketing (IM) strategies in South Africa’s beauty and personal care industry. The primary objective is to present a novel approach that digitally overlays traditional SMI marketing processes, enhancing engagement and effectiveness. A mixed-method approach was employed, integrating quantitative data from web scraping and sentiment analysis (SA) of Instagram posts with qualitative insights from the existing literature. This approach facilitated data-driven decision-making and optimised IM efficacy through technology-driven feedback analysis. The empirical findings confirmed that incorporating AI into influencer marketing (IM) campaigns significantly improves data collection and sentiment analysis, enhancing consumer engagement and purchase intent. This study underscores the transformative impact of digitalisation on marketing practices and the potential of digital tools to optimise SMI strategies in the beauty and personal care sector. This research also provides a valuable framework for marketers aiming to enhance IM campaigns, emphasising the strategic advantage of an automated response workflow based on feedback analysis. This study contributes to developing more impactful digital marketing strategies, maximising the effect of SMIs, and ensuring market competitiveness.